Peta Kemampuan Keuangan Daerah pada Pemerintahan Kota dan Kabupaten se-Jawa dan Bali Tahun 2004-2008: Metode Kuadran - Samora, Remon (Widya Mandala Surabaya Catholic University, 2010)
Regional autonomy is aimed at bringing the region’s independence in /in!1cing the region's expenditures. In its implementation, regional autonomy is still not able to realize the region's independence because each region has different characteristics so that it's required- a different policy. This study, aims to yap the regions Finance by independent and potential-regions, independent and less potential regions, non-independent and potential regions, and non_ independent and less potential region. Independent variables used are the growth ratio and the share ratio which is calculated using the District Revenue (PAD), Tax sharing (BHP), Non-Tax sharing (BHBP) and Total Expenditure